Impact of customized training program on physical attributes of badminton players - Ghosh, M.; Chakraborty, S.; Mohapatra, P.; Singh, A.; Sharma, M.; Behera, D.; Ranawat, D. (Trends in Sport Sciences, 2024)
Introduction: Badminton is one of the most popular sports which requires agility and strength. It is also a sport that needs a good amount of physical, physiological, technical and tactical assessment and training.